Tapping into the productivity potential of dairy cows in smallholder farmers in Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2019)
Mbeya, Tanzania. Dairy farmer 2019 Lukas Mwakalibwa sees his cows become healthier and produce up to 60% more milk after he adopts better husbandry and cattle feeding practices. Lukas is one of thousands of dairy farmers to reap the benefits from good herd management training under ILRI-led African Dairy Genetic Gains (ADGG) program in Tanzania. ADGG is working to unlock the potential of Tanzania's dairy sector by identifying and delivering more productive and profitable dairy cows. The ADGG program is a collaboration of Tanzanian and international partners, and is supported by the Bill & Melinda Gates Foundation & the CGIAR Research Program on Livestock. Learn more: http://news.ilri.org/category/ilri/adgg/